DNA mismatch repair mediated by Mlh1–Pms1 endonuclease-catalyzed mispair excision - Tatiana Palacio; Felipe A. Calil; Nikki Bowen; Jack D. Griffith; Christopher D. Putnam; Richard D. Kolodner (Proceedings of the National Academy of Sciences, 2025)
Eukaryotic DNA mismatch repair (MMR) involves several excision pathways, including those mediated by exonuclease 1 (Exo1) and by the flap endonuclease Rad27 (human FEN1) coupled with DNA polymerase δ. Simultaneous inactivation of both excision mechanisms causes an MMR defect that is at most 5 to 13% of that caused by complete inactivation of MMR. Here, we reconstituted nicked-strand-specific MMR with the Saccharomyces cerevisiae proteins Msh2-Msh6 or Msh2-Msh3, DNA polymerase ε, RFC, PCNA, RPA, and Mlh1-Pms1 (human Mlh1-Pms2) under conditions lacking Exo1, Rad27, or strand-displacement synthesis by DNA polymerase δ. These reactions required the Mlh1-Pms1 endonuclease activity, its activation by RFC and PCNA, and its recruitment by Msh2-Msh6 or Msh2-Msh3. MMR was mediated by nicked-strand-specific excision by Mlh1-Pms1 through formation of single-strand DNA gaps having a broad range of sizes. This reaction is consistent with genetic data demonstrating redundancy between the Exo1, Rad27, and Mlh1-Pms1 excision pathways in MMR.